#### Answer

$-1$

#### Work Step by Step

$\displaystyle \left(\frac{-2}{-3} \right)\div\left(\frac{2}{-3} \right)=$
Apply the equivalent fractions rule, $\quad \displaystyle \frac{a}{-b}=\frac{-a}{b}=-\frac{a}{b}$
$=\displaystyle \left(+\frac{2}{3} \right)\div\left(-\frac{2}{3} \right)$
Dividing two numbers with different signs:
Divide their absolute values; the sign of the result is $"-"$.
$=-\left(\displaystyle \frac{2}{3} \div \frac{2}{3} \right)$
Dividing with a fraction $\displaystyle \frac{a}{b}$ equals multiplying with the reciprocal, $\displaystyle \frac{b}{a}$.
$=-\left(\displaystyle \frac{2}{3} \cdot \frac{3}{2} \right)$
Multiply fractions:
Reduce by the common factors, 2 and 3
$=-\left(\displaystyle \frac{1}{1} \cdot \frac{1}{1} \right)$
Now, multiply the numerators and place the product over the product of the denominators.
$=-\displaystyle \frac{1}{1}$
$=-1$